A Simulation Study on Polymer Mobility Design Strategies and Their Impact on Oil Recovery Efficiency and Displacement Mechanisms - Ndaru Cahyaningtyas; Boni Swadesi; Mahruri Sanmurjana; Muhammad Rizky Rahmadsyah Lubis; Dedi Kristanto; Indah Widiyaningsih (Scientific Contributions Oil and Gas, 2025)
Polymer flooding is an effective enhanced oil recovery (EOR) technique, particularly when waterflooding alone proves insufficient in improving oil recovery. It is prominent to acquaint the principle of mobility control to understand the ability of polymer to overcome the oil displacement inefficiency of waterflooding, a requirement for a better sweep efficiency. This paper presents a comparative study of mobility control methods as critical parameters for polymer design. This paper investigates a simulation study of different simulation model to optimize polymer mobility design by comparing various mobility control methods. In this study, a compositional simulation model was built based on previous laboratory experiments validated by matching simulation results. Furthermore, to visualize the polymer displacement process, this study performs 1D, 2D, and 3D simulation models. The results indicates that polymer mobility design could affect the upstream viscosity, leading to high sweep efficiency and higher oil recovery. The study also suggests that the unit mobility ratio from the existing concept of conventional mobility control has invalid criteria to distinguish favourable and unfavourable conditions. The comparison with various mobility design methods reveals differences in recovery factors, influenced by some factors such as underlying assumptions and the specific conditions favoured by each method.